Dahschur, Ägypten. Die Arbeiten der Herbstkampagne 2019 und Frühjahrskampagne 2020 - Rosenow, Daniela (e-Forschungsberichte des DAI, 2020)
During the last two seasons work at Dahshur concentrated on continuing the excavations in the Old Kingdom settlement north of the valley temple of the Bent Pyramid. After a house was explored there in 2018 and spring 2019, fieldwork was extended further east, where a second house of similar dimension, building material and finds came to light. According to the ceramics, both buildings date to the early 4th dynasty and can probably be interpreted in the context of the building process of Sneferu’s pyramids. Further work was conducted in a cemetery of the Old Kingdom (DAM 8), the lower causeway and harbour of the Bent Pyramid and the cult chapel east of the Bent Pyramid. These monuments, partly already excavated by the DAI Cairo in the past, were photogrammetrically documented, providing a 3D-model of the structures. A new project was initiated, aiming at the conservation and touristic development of the valley temple of the Bent Pyramid.